2018
DOI: 10.1177/2047487318763823
|View full text |Cite
|
Sign up to set email alerts
|

Safety of early discharge after primary angioplasty in low-risk patients with ST-segment elevation myocardial infarction: A meta-analysis of randomised controlled trials

Abstract: Background Early discharge after successful primary angioplasty is common, but the evidence supporting the practice is still lacking. We therefore performed a meta-analysis assessing the safety of early discharge after primary angioplasty in low-risk patients with ST-segment elevation myocardial infarction (STEMI). Methods Randomised controlled trials were identified and extracted from PubMed, Embase, Cochrane Library databases and reference lists of relevant papers. Heterogeneity was analysed using the I test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…Early discharge using CADILLAC risk score showed lower mortality at day three or later in patients with lower risk score post PCI in STEMI [26]. Meta-analysis of five randomized controlled studies involving 1575 STEMI patients demonstrated the safety of early discharge in low-risk STEMI post primary PCI benefiting both patients and the healthcare system [27].…”
Section: Discussionmentioning
confidence: 99%
“…Early discharge using CADILLAC risk score showed lower mortality at day three or later in patients with lower risk score post PCI in STEMI [26]. Meta-analysis of five randomized controlled studies involving 1575 STEMI patients demonstrated the safety of early discharge in low-risk STEMI post primary PCI benefiting both patients and the healthcare system [27].…”
Section: Discussionmentioning
confidence: 99%
“…4 Here, a meta-analysis which included five randomised controlled trials on early discharge in patients with STEMI treated with primary coronary angioplasty (1575 patients in total) confirmed that shortening the length of stay was safe, with no detrimental effect on mortality and readmission rates. 5…”
Section: Safety Of Early Discharge After Primary Coronary Angioplastymentioning
confidence: 99%
“…Our tertiary center is the only cardiac center in the region providing tertiary care facility including percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) and hence receives all AMI patients deemed suitable for invasive assessment and management and this leads to huge demand on cardiac services over the few weeks of hajj time. Reduced hospital stay has been proved to reduce the hospital burden and costs [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%